Development of Discipline-Based Character Education Media on the Learning Outcomes of Fifth-Grade Students - Komang A. Laksmi; Sunardin; Hardianto (CV. Edujavare Publishing, 2026)
The limited use of learning media in schools has hindered the effective implementation of learning, particularly in integrating discipline character education. Therefore, developing learning media is expected to support the implementation of discipline character education while improving students' mathematics learning outcomes. This study aimed to develop learning media based on discipline character education that meet the criteria of validity, practicality, and effectiveness. The study employed the Research and Development (R&D) method using the 4-D development model, consisting of the define, design, develop, and dissemination stages. The development process included media design, expert validation, and field testing. The results showed that the media and design validation achieved an average score of 3.86, while the material validation obtained an average score of 3.75, both categorized as highly valid. The effectiveness test yielded a score of 94.73%, indicating that the media were highly effective, whereas the practicality test based on students' responses reached 93%, indicating that the media were highly practical. These findings demonstrate that the developed learning media based on discipline character education are valid, practical, and effective for improving mathematics learning among fifth-grade students at SD Negeri 203 Bongkamanu.